2014
DOI: 10.2478/johr-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of In Vitro Cultured MAGNOLIASP. to Nutrient Medium Composition

Abstract: The objective of this study was to assess the regeneration response of in vitro cultured Magnolia × soulangeana ‘Alexandrina’ and Magnolia liliiflora ‘Nigra’ to nutrient medium composition. In the primary culture (initiated from dormant axillary buds) combinations of Murashige and Skoog (MS) basal salts with 6-benzylaminopurine and α-naphthaleneacetic acid were tested. The primary explants of cv. ‘Alexandrina’ expressed higher regeneration rate than cv. ‘Nigra’. For both species, the regen eration was most str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
5
16
0
4
Order By: Relevance
“…1E, G). The current findings were in accordance with the report of Abdelmageed et al 2012, Nakamura et al (1995), Sokolov et al (2014) and Radomir (2012) where axillary buds were used for shoot initiation in different species of Magnolia. MS with 90% explant survivability was found to be the most effective medium for culturing axillary bud.…”
Section: Resultssupporting
confidence: 93%
“…1E, G). The current findings were in accordance with the report of Abdelmageed et al 2012, Nakamura et al (1995), Sokolov et al (2014) and Radomir (2012) where axillary buds were used for shoot initiation in different species of Magnolia. MS with 90% explant survivability was found to be the most effective medium for culturing axillary bud.…”
Section: Resultssupporting
confidence: 93%
“…GA 3 has been used to break dormancy and stimulate shoot elongation in different species of magnolias for a long time [46][47][48] . In the present study, GA 3 was found to be important for bud induction, effectively shortening the time of initiation and inducing stronger buds, which is consistent with previous reports 49,50 . However, some plants cultured in vitro did not undergo any significant growth stimulation with GA 3 51 .…”
Section: Resultssupporting
confidence: 93%
“…It has been reported that obtaining high activity of axillary buds is not easy and depends on many factors, including the composition of basal salts, plant growth regulators and the genotype (Biedermann, 1987;Kamenicka and Lanakova, 2000;Podwyszyńska et al, 2000;Parris et al, 2012;Sokolov et al, 2014). Our previous study showed that growth and development of M. × soulangiana 'Coates' in vitro was significantly influenced by the levels and ratio of cytokinin, sucrose and nitrogen salts in the MS medium (Wojtania et al, 2015).…”
Section: Introductionmentioning
confidence: 99%